Monitoring cellular Guanosine triphosphate (GTP) and GTP associated proteins - Mahran, Randa (fi=Turun yliopisto|en=University of Turku|, 2024)
Guanosine-5'-triphosphate (GTP) is an essential molecule for cell survival and function. Although free GTP plays a crucial role in several cellular processes, most studies focus solely on the protein bound GTP and its association with cancer. Efficient methods for determining cellular GTP concentration are currently lacking. Chromatography or capillary electrophoresis are commonly utilized for separation and mass spectrometry (MS) for quantification of GTP in biological samples. For monitoring GTPases and their interactions with ligands, differential scanning fluorimetry, differential scanning calorimetry, or differential static light scattering are typically utilized. However, these methods either lack sensitivity or throughput. In this PhD project, the Protein-Probe method, based on a Eu3+-chelate peptide probe that interacts with the hydrophobic core of the protein, has been developed and applied for studying different factors that affect the thermal stability of small GTPases, such as inhibitors, buffer ions and nucleotides. Furthermore, the method was explored for a better understanding of the binding specificity of the recent Food and Drug Administration approved KRASG12C covalent inhibitors to RAS GTPases. Additionally, a novel dual-labeled Förster Resonance Energy Transfer (FRET)-based peptide probe was introduced and compared to the Protein-Probe method in the thermal stability assay. The FRET-Probe technique was also applied to determine the chemical stability of proteins with different chemical denaturants. For measuring cellular GTP level, a homogenous high throughput assay was developed to measure the amount of GTP in cells utilizing a highly GTP-specific antibody. The assay yielded comparable results to those obtained with CE/MS, demonstrating a similar level of accuracy, while also exhibiting a substantial enhancement in throughput. In conclusion, this thesis work aimed at developing novel and robust methods to address the current limitations in monitoring cellular GTP concentration and to study small GTPases. The focus of the study was free GTP, recognizing its essential role in various cellular processes.

------ Guanosiini-5'-trifosfaatti (GTP) on välttämätön molekyyli solujen selviytymiselle ja toiminnalle. Vaikka vapaalla GTP:llä on ratkaiseva rooli useissa soluprosesseissa, suurin osa tutkimuksista keskittyy vain GTPaaseihin sitoutuneeseen GTP:hen ja sen linkittymisessä syövän kehittymiseen. Tällä hetkellä solun GTP-konsentraation määrittämiseksi ei ole tehokkaita menetelmiä. Käyttämällä kromatografiaa tai kapillaarielektroforeesia (CE) erotukseen ja massaspektrometriaa (MS) kvantifiointiin voidaan biologisten näytteiden GTP-pitoisuutta seurata, mutta se on melko työlästä. GTPaasien ja niiden vuorovaikutusten seurantaan käytetään tyypillisesti differentiaalista pyyhkäisyfluorimetriaa, differentiaalista pyyhkäisykalorimetriaa tai differentiaalista staattista valonsirontaa. Kaikilta näistä menetelmistä puuttuu kuitenkin herkkyys tai suorituskyky. Tästä syystä tämän opinnäytetyön tavoitteena oli kehittää uusia herkkiä ja toimintavarmoja menetelmiä GTP-pitoisuuden seurantaan ja GTPaasien tutkimiseksi uudesta näkökulmasta. Solujen GTP-tasojen mittaamiseksi kehitettiin homogeeninen tehoseulontaan yhteensopiva määritys käyttämällä GTP-spesifistä vasta-ainetta. Määritys tuotti samanlaisia tuloksia kuin vertailumenetelmänä käytetty CE/MS, mutta huomattavasti nopeammin ja helpommin. Tässä väitöskirjatyössä esiteltiin myös uusi kaksoisleimattu FRET-pohjainen peptidikoetin, jota käytettiin yhdessä aiemmin kehitetyn ”Protein-Probe” menetelmän kanssa. FRET-Probe tarjoaa saman korkean herkkyyden kuin Protein-Probe tekniikka, mutta se mahdollistaa proteiinin stabiilisuuden mittaamisen neutraalissa pH:ssa ja yhdessä vaiheessa. Protein-Probe menetelmää käytettiin pienten GTPaasien ja niiden lämpöstabiilisuuteen vaikuttavien tekijöiden tutkimiseen. Lisäksi kehitettyjä menetelmiä käytettiin FDA:n äskettäin hyväksymien kovalenttisten KRAS(G12C) inhibiittorien sitoutumisspesifisyyden, toiminnan ja resistenttiyden muodostumismekanismien tutkimiseen. FRET-Probe-tekniikkaa ei sovellettu ainoastaan proteiinien lämpöstabiilisuuden seurantaan, vaan sen osoitettiin soveltuvan myös proteiinien isotermaalisen kemiallisen stabiilisuuden seurantaan.